FUNDAMENTALIS DAN RADIKALIS ISLAM DI TENGAH KEHIDUPAN SOSIAL INDONESIA - Muslim Mufti; M. Taufiq Rahman (TEMALI : Jurnal Pembangunan Sosial, 2019)
This article discusses the origins of fundamentalism and radicalism in Indonesia. This discussion is a new challenge for social studies in Indonesia considering that this country has a population with a majority of Muslims. By taking texts from contemporary books and journals, this study describes what is the formation of fundamentalism and radicalism, why it arises, and how it develops in Indonesia. This study found that various motives and opportunities emerged in Indonesia as a cause of the emergence of fundamentalism and radicalism. Finally, this study also suggests how well the Indonesian people face the threat of fundamentalism and radicalism.